2003
DOI: 10.1097/00002030-200309050-00011
|View full text |Cite
|
Sign up to set email alerts
|

High levels of adherence do not prevent accumulation of HIV drug resistance mutations

Abstract: Increasing rates of viral suppression at high levels of adherence is balanced by increasing rates of drug resistance among viremic patients. Exceptionally high levels of adherence will not prevent population levels of drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(134 citation statements)
references
References 31 publications
2
130
1
1
Order By: Relevance
“…38,39 Viral resistance is an inevitable consequence of HAART, even in resourcerich settings with very high adherence, and should not be regarded as a barrier to scaling up but as another challenge to be faced. 40,41 Although legitimate concern exists about the spread of viral resistance during scaling up, the potential for chaotic drug supply and subsequent resistance in the absence of formal programmes is the probable alternative. In countries where few patients are exposed to suboptimum treatment and a public-health approach is taken to HIV management, the potential for widespread viral resistance could be less likely than that in resourcerich settings.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Viral resistance is an inevitable consequence of HAART, even in resourcerich settings with very high adherence, and should not be regarded as a barrier to scaling up but as another challenge to be faced. 40,41 Although legitimate concern exists about the spread of viral resistance during scaling up, the potential for chaotic drug supply and subsequent resistance in the absence of formal programmes is the probable alternative. In countries where few patients are exposed to suboptimum treatment and a public-health approach is taken to HIV management, the potential for widespread viral resistance could be less likely than that in resourcerich settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have repeatedly found that as many as half of people taking HAART are nonadaherent (Ammassari et al, 2001;Bangsberg et al, 2003;Howard et al, 2002;Ickovics et al, 2002). Adequate adherence to HAART is generally defined as taking at least 95 percent of prescribed medication (Paterson et al, 2000) which, based on a twice a day regimen, translates into missing no more than two doses per month.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that 95% of doses must be taken to achieve viral suppression (Paterson, Swindells, & Mohr, 2000), although the exact relationship between adherence to ART and viral suppression has yet to be specified (Bangsberg, Charlebois, & Grant, 2003). Inadequate adherence results in a generally poor long-term prognosis and in the emergence of treatment resistant viral strains, a public health threat.…”
Section: Introductionmentioning
confidence: 99%